Anzio [videorecording (DVD)] - Dmytryk, Edward; Mitchum, Robert; Falk, Peter, 1927-2011; Holliman, Earl, 1928-; Kennedy, Arthur, 1914-1990; Ryan, Robert, 1909-1973; Vaughan-Thomas, Wynford, 1908-1987 (RCA/Columbia Pictures Home Video, 1987)
After landing with Allied troops at Anzio, Italy in 1944, war correspondent Dick Ennis and buddy Corporal Rabinoff tell Anzio commander General Lesley that the road to Rome is wide open. But instead of heading to Rome, Lesley attempts to build a coastal stronghold, only to discover that the Germans have outflanked them by enclosing the Anzio beachhead.